Green preparation of nitrogen doped carbon quantum dot films as fluorescent probes. Issue 88 (12th December 2017) - He, Yanfei; Liang, Lina; Liu, Qinghao; Guo, Jinchun; Liang, Dong; Liu, Hongyan
Abstract : A facile and economical hydrothermal method was developed for the preparation of highly luminescent NCDs by using cabbage juice as carbon source and PP as nitrogen source. The fluorescence intensity of CA-NCDs was quenched by Fe 3+ with high sensitivity and selectivity. Abstract : To prepare nitrogen doped carbon dots (NCDs) with excellent luminescence efficiency, a facile hydrothermal method was developed using cabbage juice as the carbon source and poly ethylene polyamine (PP) as the nitrogen source. Then, as-prepared NCDs were grafted onto calcium alginate to produce calcium alginate film (CA-NCDs), and the CA-NCDs were used as a fluorescent probe. The significant quenching effect of Fe 3+ was established. The ratio of fluorescence intensity ( F / F 0 ) of the CA-NCDs had a linear relationship with the concentration of Fe 3+ within the range of 0 to 48 μM ( R 2 was 0.9947) and the detection limit was 1.4 nM. In addition, the recovery of spiked samples ranged from 98.6% to 103.1%. Most importantly, the amino-functionalized CA-NCD fluorescent probe can be successfully applied for the detection of trace Fe 3+ in water samples.